Hesperidin activates Nrf2 to protect cochlear hair cells from cisplatin-induced damage - Jintao Lou; Fan Wu; Wuhui He; Rui Hu; Ziyi Cai; Guisheng Chen; Wenji Zhao; Zhigang Zhang; Yu Si (Taylor & Francis Group, 2024)
ABSTRACTCisplatin is widely employed in clinical oncology as an anticancer chemotherapy drug in clinical practice and is known for its severe ototoxic side effects. Prior research indicates that the accumulation of reactive oxygen species (ROS) plays a pivotal role in cisplatin's inner ear toxicity. Hesperidin is a flavanone glycoside extracted from citrus fruits that has anti-inflammatory and antioxidant effects. Nonetheless, the specific pharmacological actions of hesperidin in alleviating cisplatin-induced ototoxicity remain elusive. The transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) is a critical mediator of the cellular oxidative stress response, is influenced by hesperidin. Activation of Nrf2 was shown to have a protective effect against cisplatin-induced ototoxicity. The potential of hesperidin to stimulate Nrf2 in attenuating cisplatin's adverse effects on the inner ear warrants further investigation. This study employs both in vivo and in vitro models of cisplatin ototoxicity to explore this possibility. Our results reveal that hesperidin mitigates cisplatin-induced ototoxicity by activating the Nrf2/NQO1 pathway in sensory hair cells, thereby reducing ROS accumulation, preventing hair cell apoptosis, and alleviating hearing loss.